High-temperature resistant polyborosilazanes with tailored structures - Wang, Bijie (2021)
Boron-containing organosilicon polymers are widely used under harsh environments as preceramic polymers for advanced ceramics fabrication. However, harmful chemicals released during synthesis and the complex synthesis routes have limited their applications. To solve the problems, a two-component route was adopted to synthesize cross-linked boron-containing silicone polymer (CPBCS) via a solventless process. The boron content and CPBCSs' polymeric structures could be readily tuned through controlling the ratio of multifunctional boron hybrid silazane monomers (BSZ12) and poly[imino(methylsilylene)]. The CPBCSs showed high thermal stability and good mechanical properties. The CPBCS with Si-H/C=C ratio of 10:1 showed 75 wt% char yields at 1000 °C in argon, and the heat release capacity (HRC) and total heat release (THR) are determined to be 37.9 J/g K and 6.2 KJ/g, demonstrating high thermal stability and flame retardancy. The reduced modulus and hardness of CPBCS are 0.30 GPa and 2.32 GPa, respectively. The novel polysilazanes can be potentially used under harsh environments, such as high temperatures or fire hazards.